The empty too : language and philosophy in the works of Samuel Beckett - Broomfield, Arthur (Cambridge Scholars Publishing, 2014)
This engaging and often controversial study of Beckett's works argues that, for Beckett, pure language is reality. Taking its title from a sentence in Worstward Ho, this rigorous reading of Beckett's key texts claims that what we perceive in the existential world can never be proved to exist, while language survives scrutiny, and will 'go on' to become the real, once it has been divested of its connection to the corporeal. This book draws on the major philosophers to support this thesis, but ...